Behavior of Listeria monocytogenes and Other Microorganisms in Sliced Riojano Chorizo (Spanish Dry-Cured Sausage) during Storage under Modified Atmospheres - Gonzalez-Fandos, Elena (Microorganisms, 2021)
Sliced ready-to-eat meat products packaged under modified atmospheres are often marketed since they cover consumer demands. The slicing process could be a potential risk for consumers since contamination with Listeria monocytogenes could occur during this stage. The current study evaluated the behavior of L. monocytogenes and other microorganisms in commercial sliced Riojano chorizo. This meat product was sliced and inoculated with L. monocytogenes (3.5 log CFU/g) before packaging under different atmospheres (air, vacuum, 100% N(2), 20% CO(2)/80% N(2) and 40% CO(2)/60% N(2)) and stored at 4 °C for up to 60 days. Samples were taken on days 0, 7, 21, 28 and 60 of storage. L. monocytogenes, mesophiles, Enterobacteriaceae, lactic acid bacteria, Micrococcaceae, molds and yeast counts were evaluated. Additionally, water activity, humidity and pH were determined. L. monocytogenes counts decreased in inoculated sliced chorizo during storage. Packaging conditions and day of storage influenced microbial counts. After 60 days, a significant reduction (p ≤ 0.05) in the initial Listeria contamination levels (3.5. log CFU/g) between 1.1 and 1.46 logarithmic units was achieved in the sausages packaged in modified atmosphere. The highest reductions were observed in slices packaged in 40% CO(2)/60% N(2) after 60 days of storage at 4 °C.